Employee wellness programme in clothing/ textile manufacturing companies: What are the effects? - Edries, Naila (Division of Physiotherapy, 2014)
Introduction: The prevalence of health risk behaviours is growing amongst South African employees. Health risk behaviours have been identified as a major contributor to reduced health related quality of life (HRQoL) and the increase prevalence of non-communicable diseases. Worksite wellness programmes promise to promote behaviour changes amongst employees and to improve their HRQoL. Aims: The aim of this study was to evaluate the short-term efficacy of an employee wellness programme on HRQoL, health behaviour change, levels of self efficacy, pain intensity, body mass index (BMI) and absenteeism amongst clothing and textile manufacturing employees. Methods: The study was a randomised control trial consisting of 80 participants from three clothing manufacturing companies in South Africa. The experimental group was subjected to a wellness programme based on the principles of cognitive behaviour therapy (CBT) as well as weekly supervised exercise classes over six weeks. The control group received a once-off health promotion talk and various educational pamphlets, with no further intervention. Measurements were recorded at baseline and at six weeks post-intervention. Outcome measures used included the EQ-5D, Brief Pain Inventory-SF, Stanford Exercise Behaviours Scale, Stanford Self-Efficacy Scale, Stanford Self-Rated Health Scale, BMI and absenteeism. Data Analysis: All the data were analysed with the Statistica-8 software program. Although t-tests are the most commonly used statistical method for evaluating the differences in the means between two groups (e.g. control and experimental), it assumes that the variable is normally distributed. Thus, because the ordinal data were not normally distributed, non-parametric tests were used to evaluate the differences in the medians between the two groups and to determine the level of significance. The Sign test was used in place of the paired t-test to determine the within group changes. The Mann- Whitney U test was used in place of the independent t-test to determine the difference between the two groups. Results: The experimental group consisted of 39 subjects. At six weeks post intervention the experimental group demonstrated improvement in almost every parameter. In contrast, apart from an overall decrease in time off work, there was no change noted in the behaviour of the control group. Seventy percent of the experimental group had improved HRQoL VAS scores post intervention, indicating improved perceived HRQoL. In comparison, only 58% of the control group had improved HRQoL VAS scores post intervention. v Conclusion: An employee wellness programme based on the principles of CBT combined with weekly aerobic exercise class was beneficial in improving the HRQoL and changing health-related behaviours of clothing/textile manufacturing employees.